The causal impact of gender norms on mothers' employment attitudes and expectations - Henning Hermes; Marina Krauß; Philipp Lergetporer; Frauke Peter; Simon Wiederhold (Halle Institute for Economic Research (IWH), 2025)
This field experiment investigates the causal impact of mothers' perceptions of gender norms on their employment attitudes and labor-supply expectations. We provide mothers of young children in Germany with information about the prevailing gender norm regarding maternal employment in their city. At baseline, over 70% of mothers incorrectly perceive this gender norm as too conservative – the most pronounced misperception among the various gender norms we examine. Our randomized information treatment improves the accuracy of these perceptions, significantly reducing the share of mothers who perceive gender norms as overly conservative. The treatment also shifts mothers' own labor market attitudes in a more liberal direction. Leveraging the fact that we assessed attitudes in a prior survey, we show that specifically the shifted attitude is a strong predictor of mothers' future labor-market participation. Consistently, treated mothers are more likely to plan an increase in their working hours, particularly those with existing support to facilitate their employment.
Keywords: C93; J16; J18; J22; 330; gender equality; gender norms; maternal employment; randomized controlled trial